Gaya Bahasa Amthāl Al-Qur’an - Hepni Putra (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2020)
Amthāl is one of the styles of conveying the messages of the Koran to all humans. Amthāl which is used in the Koran makes humans able to clearly visualize the material being discussed, while at the same time necessitating the nature or reality to be expressed manifest. Among the forms of amthal language style expressions used in the Koran are illustrating livestock. Livestock are one of the many animals that live side by side with human life. There is a close relationship between humans and animals that has been running for a long time, and both have an important role in world life, so it needs to be analyzed the relationship between the two represented by amthāl.